REVIEW ON THE RIGHTS TO BE CHARGED FAIRLY FOR CHASES’S SUSPECT DUE TO THE PUBLIC ATTENTION IN TRIAL SYSTEM INDONESIAN LAW - Dian Narwastuty; Arman Tjoneng; Evi Hanias (Jurisprudentie: Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2021)
A trial is an important stage in proofing for each party. Each of the party will submit any evidences to support their arguments of evidence so that the panel of judges can examine and judge cases clearly. Each party has the right to undergo a form of trial that is fair (fair trial). In this paper, the writing team focuses on the issue of the defendant's right to a neutral trial process. But the reality is that in several criminal cases that attract public attention, there is often a neglect of the defendants' rights to undergo a trial that is free from public pressure, excessive media coverage, and even the accompanying opinion on a case. This has resulted in a flaw in law enforcement where the law should be able to provide the same service and sense of security to every justice seeker. This lame criminal law will result in the presence of an unfair decision for both the victim and the accused.This research used normative research with comparative approach and Conceptual approach. These approachs are used to examining all laws and regulations related to the legal issue that are imposed in this research. Research is elaborate with the views and doctrines that are developing in in law. The data used are secondary data obtained by library research and primary data obtained by conducting interviews with respondents and litigation institutions. The conclution that can be drawn from the discussion are there is a loop in our Criminal Procedural system. Especially in treating a case with a huge public attention. It urges to be fixing, so the dignity of the trial of courtroom will be stay. The massive broadcasting for the live trial should be re-considered. The broadcaster right should not be offending the courtroom dignity. The trial may keep the media in courtrooms as long as to keep the fairness of trial.